2022
DOI: 10.3389/fimmu.2022.837497
|View full text |Cite
|
Sign up to set email alerts
|

Baicalein—A Potent Pro-Homeostatic Regulator of Microglia in Retinal Ischemic Injury

Abstract: Retinal ischemia is a common cause of many retinal diseases, leading to irreversible vision impairment and blindness. Excessive neuroinflammation, including microglial activation and T-cell responses, has been identified as a critical factor associated with neurodegeneration in retinal ischemia. Baicalein is a natural flavonoid reported to have broad anti-inflammatory and neuroprotective bioactivities. Herein, the effects of baicalein on microglia activation in vitro and in vivo were investigated. We found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…To study the functional effect of ES in the ONC model, electroretinogram positive scotopic threshold response (pSTR) were recorded 27 . Mice were dark‐adapted overnight and anesthetized with an intraperitoneal injection of ketamine (120 mg/kg)/xylazine (20 mg/kg).…”
Section: Methodsmentioning
confidence: 99%
“…To study the functional effect of ES in the ONC model, electroretinogram positive scotopic threshold response (pSTR) were recorded 27 . Mice were dark‐adapted overnight and anesthetized with an intraperitoneal injection of ketamine (120 mg/kg)/xylazine (20 mg/kg).…”
Section: Methodsmentioning
confidence: 99%
“…Using episcleral vein occlusion, a significant loss of RGCs and downregulation of PA2G4 expression have been shown in aged rats receiving cauterization when compared with controls [85]. Recently, the neuroprotective effects of Ba against retinal functional and morphological damages resulting from retinal ischemia reperfusion injury have also been demonstrated [86]. It was found that Ba alleviates the expression of proinflammatory cytokines including TNF-α, IL-6, and IL-1β in mouse microglia, supporting its biomedical significance for glaucoma treatment as elevated levels of TNF-α, IL-6, and IL-1β are observed in the TM of glaucoma patients [87].…”
Section: Other Properties Of Ba In Potentially Regulating Tm Cell Fun...mentioning
confidence: 99%
“…The therapeutic potential of natural herbal treatments for ischemic retinal damage has become increasingly evident in recent years. These medicines, including Scutellaria , lutein, and wolfberry, have antioxidant, anti-inflammatory, and anti-excitotoxic properties and can maintain the permeability of the retinal blood supply ( Li et al, 2009 ; He et al, 2014 ; Pan et al, 2022 ). In addition, various natural extracts, such as resveratrol, Ginkgo biloba extract, and curcumin, have been shown to protect the CNS and exhibit neuroprotective properties ( Yuan et al, 2014 ; Wang et al, 2017a ; Luo et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Scutellaria baicalensis is the main component of many traditional Chinese medicines, and its safety and efficacy in clinical applications have been demonstrated. Baicalin exerts potent anti-inflammatory effects by reducing the induction of proinflammatory cytokines and inhibiting PI3K/NF-κB phosphorylation ( Pan et al, 2022 ). Oroxylin A is a flavonoid that regulates nuclear factor E2-related factor 2 (Nrf2) and its antioxidant enzymes NAD(P)H quinone oxidoreductase 1 and home oxidoreductase 1 (HO-1).…”
Section: Introductionmentioning
confidence: 99%